THE ROLE OF MENTAL WORKLOAD IN INVESTING QUALITY OF LIFE AMONG WORKERS IN THE PHOSPHORIC ACID INDUSTRY - Syaiful, Dayinta Annisa; Martiana, Tri; Paskarini, Indriati; Ankhofiya, Deanida (The Indonesian Journal of Public Health, 2024)
Introduction: Every workplace has potential hazards, one of which is psychological hazards, namely work stress. The stress felt by workers can interfere with their work activities if not controlled immediately. In Indonesia, 11.6–17.3% of the 150 million adult population suffers from stress at work. Moreover, job stress can be caused by various factors. Aims: To assess workers' quality of work life by analyzing the relationship between mental workload and work stress. Moreover, this research investigates the individual characteristics, mental workload level, and stress level between workers. Methods: This research is a quantitative study using an observational design and a cross-sectional technique. The participants in this study were all 35 maintenance personnel. Mental workload and work stress are assessed using NASA-TLX and DASS-21 questionnaire, respectively. Results: The collected   data   are statistically analyzed using the Spearman correlation test and the Cramer contingency coefficient correlation test.  The results showed that mental workload has a strong relationship with work stress which is in the strong category (r= 0,679) and the direction of the relationship is unidirectional. Conclusion: The conclusion of this study is that the higher the mental workload possessed by workers, the higher the level of perceived work stress. Therefore, the company can reduce work stress by conducting both individual and organizational strategies